A feasibility study of the 1.5-axis tracking model in utility-scale solar PV plants. (1st March 2021) - Wong, Junying; Bai, Feifei; Saha, Tapan Kumar; Tan, Rodney H.G.
Abstract: Many solar tracking technologies have been developed with the aim of improving the energy performance of solar PV installations. Among these, single-axis tracking (SAT) systems give good economic prospect for ground-mounted PV plants but experience inevitable power loss when the trackers diverge from the incident solar irradiance during winter. The 1.5-axis tracking (1.5AT) model is developed in recent years to achieve a balance between the benefits and shortcomings of the SAT and dual-axis tracking (DAT) systems. Despite the anticipated superiority of the 1.5AT, there is a lack of literature on the methodology to analytically study the potential and feasibility of the 1.5AT model, especially from a global perspective. In this paper, a comprehensive feasibility study has been conducted to evaluate the energy performance and shading analysis of the 1.5AT model. The developed methodology serves as a general benchmark to explore the prospects of the 1.5AT model at different geographical locations and seasons. This encourages further research and deployment of the 1.5AT model as a potential alternative to improve the return of investment for various PV system stakeholders.